On-the-job Training to strengthen the operational capacities of NMHSs to produce New Generation of Seasonal Forecasts in West Africa and the Sahel - Houngnibo, Mandela C.; Ali, Abdou; Minoungou, Bernard; Seidou Sanda, Ibrah; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The on-the-job training is a designed one-month capacity-building program to National Meteorological and Hydrological Services (NMHSs) from West African and Sahel countries (29 participants from 13 countries, including 11 non-AICCRA countries) on the full range of seasonal and sub-seasonal forecasting methodologies. The on-the-job training provided participants with practical experience in using WAS_S2S tools along with tools like PyCPT and Xcast, while it also introduced them to AI-based approaches. Additionally, the training focused on evaluating the different methodologies, helping participants understand the strengths and limitations of each approach and how they can be applied in their respective national contexts.